High-Resolution Microendoscope Images of Middle Ear Cholesteatoma and Surrounding Tissue: Evaluation of Interobserver Concordance. (April 2014) - Bradley, James; Jiang, Nancy; Levy, Lauren; Richards-Kortum, Rebecca; Sikora, Andrew; Smouha, Eric
Objective: Investigate how accurately otolaryngologists could differentiate between images obtained with high-resolution microendoscopy (HRME) of ex vivo cholesteatoma specimens and surrounding middle ear epithelium. Study Design: HRME images of surgically resected cholesteatoma and middle ear epithelium were obtained and otolaryngologists classified these images. Setting: Tertiary medical center. Subjects and Methods: Resected cholesteatoma and middle ear epithelium were stained with a contrast agent, proflavine, and HRME images were captured. Specimens were sent for standard histopathology and compared with HRME images. Quality-controlled images were used to assemble a training set. After viewing training images, otolaryngologists without prior cholesteatoma HRME experience reviewed and classified test images. Results: Ten cholesteatoma and 9 middle ear specimens were collected, of which 17 representative cholesteatoma and 19 middle ear epithelium images were extracted for a testing set. Qualitative analysis for concordance between HRME images and histological images yielded a strong correlation between modalities. The mean accuracy of all reviewers in correctly identifying images was 95% (95% confidence interval [CI], 92%-98%). The sensitivity to correctly detect cholesteatoma images was 98% (95% CI, 93%-100%), and the specificity was 92% (95% CI, 87%-97%). The Fleiss kappa interrater reliability score was 0.83, (95% CI, 0.77-0.89). Conclusions: Medical professionals can quickly be trained to accurately distinguish between HRME images of cholesteatoma and normal middle ear epithelium, both of which have distinct imaging characteristics. Real-time HRME optical imaging can potentially improve the results of otologic surgery by allowing for extirpation of cholesteatomas while eliminating residual disease.